2014
DOI: 10.5505/sakaryamj.2014.52244
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Endoscopic Gastrostomy; Experience of two clinics

Abstract: Amaç: Perkütan endoskopik gastrostomi ( PEG ) gastrostomi yöntemleri içinde en sık ve en basit uygulanan minimal invaziv yötemdir. Çalışmamızda PEG uygulanan hastaların sonuçları ve reflü hastalığı ile ilişkisi değerlendirildi. Materyal Metod: Ocak 2010 -Ocak 2012 tarihleri arasında iki çocuk cerrahisi merkezinde perkutan endoskopik gastrostomi kateteri takılan 13 hastanın dosyası geriye dönük incelendi. Bulgular: Hastaların 6'sı erkek ( % 46 ), 7'si kız ( % 54 ) idi. Yaş ortalaması 3,5 yıl idi. Hastaların ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Major and minor complications may occur after the PEG procedure. Studies have reported complication rates ranging from 4% to 13.6% (13). In our study, complications occurred in 11 patients (13.1%), with no patients experiencing a major complication.…”
Section: Discussionmentioning
confidence: 44%
“…Major and minor complications may occur after the PEG procedure. Studies have reported complication rates ranging from 4% to 13.6% (13). In our study, complications occurred in 11 patients (13.1%), with no patients experiencing a major complication.…”
Section: Discussionmentioning
confidence: 44%
“…It was detected that skull base fractures were anatomically on a single site in 44.2% of the cases, on multiple sites in 55.8% of the cases; no edema was detected in 77.5% of the patients; contusion was observed in 19.6% of the cases; epidural hematoma, subdural hematoma, subarachnoid bleeding and intracranial hematoma were detected in 31.9%, 14.5%, 24.6% and 6.5% of the cases respectively. A previous research on skull base fracture reported higher incidence of intracranial hemorrhage in the moderate head injury group than mild and severe head injury groups [14]. It was found in the same study that skull base fractures appeared on the anterior fossa were more likely to cause single lesion of traumatic intracranial hemorrhage when compared with other groups.…”
Section: Discussionmentioning
confidence: 55%
“…Basillary skull fractures are more common in younger individuals due to their tendency to perform risky activities [13]. A previous study demonstrated that 64.7% cases of skull base fractures had injury to the anterior fossa of the skull [14]. An earlier study reported that the most common causes of skull injuries were traffic accidents (59%), fall (13%) and bicycle accident (12%) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan iki çalışmada da ebeveynlerin sağlık hizmetlerinde kaynak bulmada ve tek başlarına çocukların bakımını devam ettirmekte kendilerini yetersiz hissettikleri (5), herhangi bir minör komplikasyon gerçekleştiğinde endişelendikleri, çocuğun günlük bakımlarını (banyo, üst değiştirme vb.) yaparken zorlanabildikleri ve bununla baş etmede güçlükler yaşadıkları bildirilmiştir (17).…”
Section: Introductionunclassified